EVALUATION OF THE APPLICATION OF E-HDW APPLICATION AS A STUNTING CONVERGENCE DATA COLLECTION AND MAPPING TOOL IN NGAMPELSARI VILLAGE - Kurnaini, Alfiatus Fadjar; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The e-Human Development Worker (e-HDW) application is an innovation from the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration designed to assist data collection and mapping of stunting targets at the village level. This study aims to evaluate the effectiveness of the e-HDW application in supporting efforts to accelerate stunting reduction in Ngampelsari Village. Method: The research method used is qualitative with a descriptive analysis approach. Data were collected through interviews, observation, and documentation, then analyzed using William N. Dunn's policy evaluation model, which includes indicators of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. Result: The results showed that the e-HDW application has contributed to accelerating the process of data collection and monitoring of stunting, with a more structured recording system than the manual method. However, its implementation is still constrained such as slow application access during working hours and imperfections in the automatic data update feature. In addition, the distribution of application socialization is still not optimal, causing delays in data entry in some areas. Novelty: Therefore, it is necessary to improve system infrastructure, server optimization, and wider socialization so that this application can be maximally utilized in supporting the acceleration of stunting reduction programs.